Synthesis of angiotensin-converting enzyme (ACE) inhibitors: an important class of antihypertensive drugs - Lima Dênis Pires de (Química Nova, 1999)
This report outlines the discovery, the design and development of new compounds, and, structure-activity relationships for this drug category. Updated approaches to planned syntheses of new worthy ACE-inhibitors are also exploited.